Dosimetric characteristics of LKB:Cu,P solid TL detector - Hashim, S.; Alajerami, Y. S. M.; Ghoshal, S. K.; Saleh, M. A.; Saripan, M. I.; Kadir, A. B. A.; Bradley, D. A.; Alzimami, K. (Elsevier, 2014)
The dosimetric characteristics of newly developed borate glass dosimeter modified with lithium and potassium carbonate (LKB) and co-doped with CuO and NH4H2PO4 are reported. Broad peaks in the absence of any sharp peak confirms the amorphous nature of the prepared glass. A simple glow curve of Cu doped sample is observed with a single prominent peak (Tm) at 220°C. The TL intensity response shows an enhancement of ~100 times due to the addition of CuO (0.1mol%) to LKB compound. A further enhancement of the intensity by a factor of 3 from the addition of 0.25mol% NH4H2PO4 as a co-dopant impurity is attributed to the creation of extra electron traps with consequent increase in energy transfer of radiation recombination centers. The TL yield performance of LKB:Cu,P with Zeff ≈8.92 is approximately seventeen times less sensitive compared to LiF:Mg,Ti (TLD-100). The proposed dosimeter shows good linearity up to 103Gy, minimal fading and photon energy independence. These attractive features offered by our dosimeter is expected to pave the way towards dosimetric applications.